1995
DOI: 10.1002/mpo.2950240513
|View full text |Cite
|
Sign up to set email alerts
|

Veno‐occlusive Disease of the Liver After Chemotherapy for Rhabdomyosarcoma: Case Report With a Review of the Literature

Abstract: We describe the case of a 3-year-old girl who developed veno-occlusive disease of the liver while receiving chemotherapy for parameningeal rhabdomyosarcoma. After suffering lethargy and oral mucosal bleeding for one day, the patient exhibited a sudden weight gain and refractoriness to platelet transfusions. Symptoms rapidly worsened with elevation of liver enzymes, bleeding diatheses, and respiratory failure. An ultrasound scan of the liver demonstrated reversed flow in the portal vein. Maximal supportive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…It usually occurs within the first 3 weeks of marrow infusion. Risk factors for post-transplant VOD are pre-transplant hepatitis, age over 15 years, and underlying malignancy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It usually occurs within the first 3 weeks of marrow infusion. Risk factors for post-transplant VOD are pre-transplant hepatitis, age over 15 years, and underlying malignancy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Adachi et al described an 1-year-old boy who developed VOD of liver after receiving vincristine (1.5 mg/m 2 given twice), actinomycin D (15 µg/kg given 5 times), and cyclophosphamide (600 mg/m 2 given once) [12]. Kanwar et al described a 3.8-year-old girl who developed hepatic VOD while receiving VAC regimen of the IRS-IV for parameningeal rhabdomyosarcoma [6]. D'Antiga et al reported 6 patients (4 Wilms tumor, 1 clear cell sarcoma, and 1 rabdomyosarcoma case) who developed hepatic VOD during treatment with actinomycin D and vincristine alone.…”
Section: Discussionmentioning
confidence: 98%
“…In the past two decades, VOD has been increasingly recognized as a complication of conventional chemotherapy with or without abdominal irradiation, which most frequently occurs in Wilms tumor cases 616 E. Cecen et al who received vincristine and actinomycin D [2][3][4]. But only few cases have been reported in children treated with same agents for rhabdomyosarcoma [5,6].…”
mentioning
confidence: 97%
“…Toxicity was more likely to occur early in treatment, although the incidence was lower in patients who tolerated their first course of therapy [9]. Other major risk factors appear to be the presence of Wilms tumour, as opposed to other tumour types, and Act D dose intensity [5, 10]. Bearing these factors in mind, it is a concern that for many well established drugs such as Act D, currently used dosing guidelines are founded largely on empirical experience, as opposed to being based on a sound knowledge of the clinical pharmacology of the drug.…”
Section: Introductionmentioning
confidence: 99%